Flipped Classroom Meta-Analysis of Critical Thinking Skills and Learning Outcomes in High School Physics Learning - Meili Dwi Indriyani; Stepanus Sahala Sitompul; Ray Cinthya Habellia (Universitas Lambung Mangkurat, 2023)
The main objective of this research is to analyze the effect of the flipped classroom on critical thinking skills and learning outcomes in high school physics learning. This study's specific objective is to determine the effect size and the influence of research characteristics from various literature articles. The population in this study amounted to 21 research articles, and then the research sample was taken from the population using a purposive sampling technique. The research instrument used coding sheets. The results of the meta-analysis of this study indicated that the flipped classroom could affect critical thinking skills and student learning outcomes in high school physics learning. The average effect size of the flipped classroom model on critical thinking skills in high school physics learning was 1.964, and the average effect size of the flipped classroom model on learning outcomes in high school physics learning was 2.058. This study analyzed eight research characteristics in the article that were thought to influence critical thinking skills and learning outcomes. Among them were the gender of the researcher, the research university, the research location, the physics material, the type of research, the sample size used, data collection tools, and statistical tests. The results of the analysis showed the characteristics of research articles that influence critical thinking skills and learning outcomes: sample size, researcher's gender, data collection tools, and materials, making these characteristics need to be considered in research.